Energy-based considerations for the seismic design of ductile and dissipative glass frames. Issue 125 (October 2019) - Santarsiero, Manuel; Bedon, Chiara; Moupagitsoglou, Kosmas
Abstract: Current design standards for seismic resistant buildings provide recommendations for the advanced analysis of several structures subjected to earthquakes, but no specific details are given for structural glass systems. Compared to other constructional materials, and given the actual fail-safe design goals for earthquake resistant systems, critical design issues for glazed structures may derive from the lack of appropriate resistance but also from the limited accommodation of displacement demands. Such an outcome is strictly related to the intrinsic brittleness of glass, as well as to the typical geometrical and mechanical features of glass structures. As a result, joints and restraints can have a key role for design optimization purposes. This paper presents an energy-based analytical approach in support of the efficient design and the reliable structural performance evaluation of glass systems in seismic regions. Special care is spent for glass frames, giving evidence of their potential ductile and dissipative behaviour. More in detail, the proposed formulation takes advantage of the dissipative capacity of steel connections, for the non-linear structural analysis of seismic resistant glass frames. The reliability of the analytical method is first discussed via a practical application. Refined Finite Element (FE) numerical simulations are also presented, in support of the assessment and validation of the analytical findings. The collected results show that the combination of appropriate structural design assumptions and advanced non-linear analysis techniques can allow the achievement of highly efficient and satisfactory seismic performances of glass frames, even in the same order of other common structural systems. Highlights: Current design codes and standards for seismic resistant buildings do not provide specific provisions for structural glass systems Major issues in design are related to the capacity of accommodate large displacements, without damage The lack of design recommendations typically results in over-design of inefficient, non-dissipative structures The paper explores the seismic performance of glass portal frames, based on energy considerations Analytical and numerical studies are reported for a case-study system, giving evidence of the high potential of structural glass even in seismic conditions